Improving oxidative stress resilience in plants - Kerchev, Pavel I; Van Breusegem, Frank (The Plant journal, 2022)
Originally conceived as harmful metabolic byproducts, reactive oxygen species (ROS) are now recognized as an integral part of numerous cellular programs. Thanks to their diverse physicochemical properties, compartmentalized production, and tight control exerted by the antioxidant machinery they activate signaling pathways that govern plant growth, development, and defense. Excessive ROS levels are often driven by adverse changes in environmental conditions, ultimately causing oxidative stress. The associated negative impact on cellular constituents have been a major focus of decade-long research efforts to improve the oxidative stress resilience by boosting the antioxidant machinery in model and crop species. We highlight the role of enzymatic and non-enzymatic antioxidants as integral factors of multiple signaling cascades beyond their mere function to prevent oxidative damage under adverse abiotic stress conditions.
Keywords: Plants; oxidační stres; antioxidancia; reaktivní formy kyslíku; Droughts; signální transdukce; stress resilience; oxidative stress; fyziologie rostlin; Signal Transduction; rostliny; Stress, Physiological; oxidace-redukce; Reactive Oxygen Species; Antioxidants; Plant Physiological Phenomena; Oxidation-Reduction; reactive oxygen species; Oxidative Stress; fyziologický stres; antioxidants; období sucha